Laju tangkap dan hasil tangkapan bagan tancap dengan menggunakan lampu Light Emitting Diode (LED) di Perairan Pangkajene dan Kepulauan - Adnur Cahyu Fatimah; Muhammad Kurnia; Musbir Musbir (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2022)
This study aims to find out the catch rate and fcomposition of catches and frequency of appearance. This study was carried out in June - October 2021 by following one unit of Fixed Lift-net tool as many as 30 trips and 44 hauling times each 10 trips for each lamp color. White Light Capture Rate 5.92 kg /h, yellow light 2.62 kg /h and blue light 1.57 kg/h. The results of the study conducted obtained the composition of the catch for 30 trips 44 hauling using LED aids in white, yellow and blue obtained as much as 1113.5 kg, white light catch 669.3 kg, yellow light 274.4 kg while blue light 169.8 kg. The fish species with the most frequency of occurrence out of 44 capture hauling were squid (Loligo Sp) 93.18%, Lemuru (Sardinela Fimbriata) 81.82%, Peperek (Leiognathur Equulus) 56.82%, Selanget (Anodontosoma Chacun) 50.00% and Selar (Selaroides Leptolepis) 34.09%.Â